Pengembangan Buku Ajar IPS SD Tentang Tokoh–Tokoh Islam Pada Peristiwa Proklamasi Kemerdekaan - Adawiyah, Robi'atul; Nataria Wahyuning Subayani; Nanang Khoirul Umam (Universitas Ngudi Waluyo, 2024)
The purpose of this study is to develop the teaching book of important moeslim figures during the proclamation of indepence in MIS Al-Islami Tiremenggal, during the school year 2022/2023. The model of development used inthis study is the developing mode ADDIE, which consists of five stages which are Analysis, Design, Development, Implementation,and Evaluation. The subject used for this study are students in fifth grade in MIS Al-Islami. The data was gatheres for this study by using validation paper from a linguist, material or content expert, and graphic artist along wit questionnaire sheets for students responses. Based on the result of linguist data analysis that is developed are on very valid criteria with a score of 94,44%. The result of the material analysis that is developed are on very valis criteria with a score 90,91%. The developed data of graphic artist data analysis resulted on very valid criteria with a score 97,53%. The testing conducted by the expert resulted with a score of 92,16% on very good criteria. The result of the development of the teaching book of important moeslim figures during the proclamation of independence using the ADDIE model is concluded on very valid and very good criteria. Abstrak Penelitian ini bertujuan untuk mengembangkan buku ajar tokoh-tokoh islam pada peristiwa proklamasi kemerdekaan di MIS Al-Islami Tiremenggal tahun ajaran 2022/2023. Model pengembangan yang digunakan dalam penelitian ini adalah model pengembangan ADDIE yang terdiri dari lima tahapan yaitu Analysis, Design, Development, Implementation, dan Evaluation. Subjek pada penelitian ini adalah peserta didik kelas V MIS Al-Islami Tiremenggal. Teknik pengumpulan data pada penelitian menggunakan lembar validasi dari ahli bahasa, ahli materi atau isi dan ahli kegrafikaan serta lembar angket respon peserta didik. Berdasarkan hasil analisis data ahli bahasa yang dikembangkan berada pada kriteri sangat valid dengan skor sebesar 94,44%. Hasil analisis materi yang dikembangkan berada pada kriteria sangat valid dengan skor sebesar 90,91%. Hasil analisi data ahli kegrafikaan yang dikembangkan berada pada kriteria sangat valid dengan skor sebesar 97,53%. Hasil uji coba yang dilakukan peneliti memproleh skor sebesar 92,16% dengan kriteria sangat baik. Buku ajar tokoh-tokoh islam pada peristiwa proklamasi kemerdekaan yang dikembangkan dengan menggunakan model ADDIE dapat disimpulkan memenuhi kriteria valid dan sangat baik